2016
DOI: 10.1371/journal.pmed.1002003
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Homicide of Neonates, Infants, and Children under 5 y in South Africa: Results from the Cross-Sectional 2009 National Child Homicide Study

Abstract: BackgroundHomicide of children is a global problem. The under-5-y age group is the second largest homicide age group after 15–19 y olds, but has received little research attention. Understanding age and gender patterns is important for assisting with developing prevention interventions. Here we present an age and gender analysis of homicides among children under 5 y in South Africa from a national study that included a focus on neonaticide and infanticide.Methods and FindingsA retrospective national cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…This finding is supported by the national child homicide study showing that SA had one of the highest reported rates of neonaticide globally. [9] Neonaticide is the killing of a newborn within the first 6 days of life, and infanticide the killing of a child in the first year of life. Both these acts are a form of child abuse, whether the killing was deliberate or the death due to a deliberate omission of care, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by the national child homicide study showing that SA had one of the highest reported rates of neonaticide globally. [9] Neonaticide is the killing of a newborn within the first 6 days of life, and infanticide the killing of a child in the first year of life. Both these acts are a form of child abuse, whether the killing was deliberate or the death due to a deliberate omission of care, e.g.…”
mentioning
confidence: 99%
“…when a baby is abandoned without care, protection or supervision. [9] Infanticide or abandonment of a newborn is far more common than the CDR pilot suggests, as many infants are 'dumped' in sewers, refuse dumps and dirt bins, and the pilot only identified remains brought to a mortuary. Despite SA's liberal termination of preganancy legislation and the availability of community-based contraception services, it would appear that we are not meeting the needs of large numbers of women.…”
mentioning
confidence: 99%
“…The rate of infanticide in SA is estimated to be among the highest reported rates globally, at 28.4/100 000 live births, [1] only surpassing a reported rate for Dar es Salaam, Tanzania. [19] Abandonment and injury deaths of infants were found to be common immediately after birth.…”
Section: Discussionmentioning
confidence: 91%
“…[1] The first national prevalence study on child abuse confirms excessive rates of child maltreatment, with one-third of children reporting experiences of sexual and/or physical abuse during childhood. [20] The insidious nature of violence against children highlights the need to prioritise prevention efforts to break the cycle of child maltreatment, particularly in the home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation